Power Relations between Media and Politics in Indonesia - Syah Putra, Dedi Kurnia (Jurnal Ilmu Sosial Indonesia (JISI), 2024)
Abstract. The 2024 General Election in Indonesia has become a central arena for the complex dynamics between media and politics. In-depth qualitative research reveals that the relationship between media and political parties is key to understanding how political information is conveyed to the public. Mass media, both print and electronic, plays a strategic role in shaping public perceptions of political parties, candidates, and campaign issues. Social media, with its two-way interaction and rapid dissemination, strengthens the direct connection between political parties and voters. The media not only serves as a conduit for information but also as a primary platform for political discourse, including comparisons of political parties, assessments of candidates, and analysis of campaign programs. The relationship between media and political parties is characterized by cooperation, competition, and occasional conflict. Political parties actively engage in crafting campaign messages and coordinating media interviews, while social media plays a pivotal role in their communication strategies. This dynamic raises questions about the independence of the media and how political parties leverage it to achieve their political objectives. On one hand, the media acts as a critical watchdog; on the other hand, political parties seek to use the media to amplify campaign messages and shape narratives that align with their interests. In conclusion, the relationship between media and political parties in Indonesia’s 2024 General Election forms a complex dynamic. The media plays a strategic role in shaping public opinion, while political parties actively utilize it to achieve their political goals. Keywords: Political Media Relation, Political Party, Pemilu 2024 Abstrak. Pemilu 2024 di Indonesia menjadi arena utama bagi dinamika kompleks antara media dan politik. Penelitian kualitatif mendalam mengungkapkan bahwa hubungan media dan partai politik menjadi kunci memahami bagaimana informasi politik disampaikan kepada publik. Media massa, baik cetak maupun elektronik, memiliki peran strategis membentuk persepsi publik terhadap partai politik, kandidat, serta isu-isu kampanye. Media sosial, dengan interaksi dua arah dan penyebaran yang cepat, memperkuat hubungan langsung antara partai politik dan pemilih. Media tidak hanya berfungsi sebagai penyampai informasi, tetapi juga menjadi platform utama untuk diskusi politik, termasuk perbandingan partai politik, penilaian terhadap kandidat, dan analisis program kampanye. Relasi antara media dan partai politik ditandai oleh kerja sama, persaingan, dan kadang-kadang konflik. Partai politik secara aktif terlibat dalam penyusunan pesan kampanye dan koordinasi wawancara media, sementara media sosial berperan sebagai elemen kunci dalam strategi komunikasi mereka. Dinamika hubungan ini menimbulkan pertanyaan tentang independensi media dan bagaimana partai politik memanfaatkannya untuk mencapai tujuan politik mereka. Di satu sisi, media berfungsi sebagai pengawas yang kritis; di sisi lain, partai politik berusaha menggunakan media untuk memperkuat pesan kampanye dan membentuk narasi yang sesuai dengan kepentingan mereka. Kesimpulannya, hubungan antara media dan partai politik dalam Pemilu 2024 di Indonesia membentuk dinamika yang kompleks. Media memainkan peran strategis dalam membentuk opini publik, sementara partai politik secara aktif memanfaatkannya untuk mencapai tujuan politik mereka. Kata Kunci: Relasi Media Politik, Partai Politik, Pemilu 2024